PERKEMBANGAN BAHASA ANAK USIA 5-6 TAHUN: SIBLING RIVALRY FENOMENOLOGI - Hani Nirrana Amalia; Rhoudatun Naimah; Gita Fannia Nadillah; Rahma Rizkiya Septiana; Adharina Dian Pertiwi (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This research aims to provide a deeper understanding of the dynamics of sibling rivalry and how this can affect the language skills of children aged 5-6 years. This study used qualitative research with a sample of 13 parents who had children aged 5-6 years. The research results show that the way parents care for, guide and direct varies depending on the parenting style applied by each parent to their child. As well as sibling rivalry which has an impact on the language of children aged 5-6 years. Keywords:  Sibling rivalry ; 5-6 years ; Children